Threshold-impeded stochastic production: how noise interacts with disruptive thresholds to affect the production output in fluctuating environments - Merten, Daniel Christopher; Lesne, Annick; Uygun, Yilmaz; Hütt, Marc-Thorsten (Frontiers in Industrial Engineering, 2024)
Threshold-impeded stochastic production: How noise interacts with disruptive thresholds to affect the production output in fluctuating environments.Production systems are bound to operate in stochastic conditions. Prominent sources of performance-reducing uncertainty are constituted by machine failures, decision errors, and fluctuating supplies. This article offers a novel approach to uncertainty through modelling and simulation of nonlinear production systems. In particular, the authors consider production systems where the output is drastically reduced when a resource of fluctuating input values reaches an upper threshold. The article introduces minimal models of such threshold-impeded stochastic production (TISP) systems and the system performance (i.e. the output) is analyzed as a function of system parameters (e.g. the type of nonlinearity) and noise input features (e.g. the distribution width or time correlations). Applications to steel manufacturing via continuous casting and power generation through wind turbines are discussed in detail. The simulation experiments illustrate that especially the extent of the input fluctuations affects the output performance which is why the authors recommend that TISP system operators counterbalance such fluctuations if possible.